Rheumatoid arthritis is still expensive in the new decade: a comparison between two early RA cohorts, diagnosed 1996–98 and 2006–09. (2nd September 2016) - Hallert, E; Husberg, M; Kalkan, A; Bernfort, L
Abstract : Objectives : To calculate total costs during the first year after diagnosis in 463 patients with early rheumatoid arthritis (RA) included during 2006–09 (T2) and compare the results with a similar cohort included in 1996–98 (T1). Method : Clinical and laboratory data were collected regularly in both cohorts, and patients completed biannual questionnaires reporting health care utilization and number of days lost from work. Results : Disease activity was similar in both cohorts T1 and T2 at inclusion. Significant improvements were seen during the first year in both cohorts but were more pronounced in T2. Outpatient care increased and hospitalization decreased in T2 compared with T1. Almost 3% of patients had surgery in both cohorts, but in T2, only women had surgery. Drug costs were higher in T2 than in T1 (EUR 689 vs. EUR 435). In T2, 12% of drug costs were direct costs and 4% were total costs. The corresponding values for T1 were 9% and 3%. In T1, 50% were prescribed disease-modifying anti-rheumatic drugs (DMARDs) at inclusion, compared to T2, where prescription was > 90%. Direct costs were EUR 5716 in T2 and EUR 4674 in T1. Costs for sick leave were lower in T2 than in T1 (EUR 5490 vs. EUR 9055) but disability pensions were higher (EUR 4152 vs. EUR 2139), resulting in unchanged total costs. In T1, direct costs comprised 29% and indirect costs 71% of the total costs. The corresponding values for T2 were 37% and 63%. Conclusions : The earlier and more aggressive treatment of RA with traditional DMARDs in T2 resulted in better outcomes compared to T1. Direct costs were higher in T2, partly offset by decreased sick leave, but total costs remained unchanged.